PENGUATAN KARAKTER WIRAUSAHA SANTRI BERBASIS PENDIDIKAN PESANTREN DARUL AMANAH - Nur Khasan; Iman Fadhilah; Ali Imron (Al-Mudarris, 2026)
This study examines the formation of Islamic entrepreneurial character among santri at Pondok Pesantren Darul Amanah through a tarbiyah-based educational approach. Unlike conventional entrepreneurship education, which primarily emphasizes economic independence, pesantren-based entrepreneurship places spiritual values, moral responsibility, and social benefit (maslahah) as its fundamental principles. This study aims to analyze how the pesantren educational system shapes students’ entrepreneurial character through the integration of religious learning, daily practices, and the internalization of Islamic values. The research employed a qualitative approach with a field research design. Data were collected through observation, in-depth interviews, and documentation. The data were analyzed using thematic analysis by employing Islamic educational principles, particularly tarbiyah, akhlaq, and maqasid al-shariah, as interpretative frameworks. The findings reveal that the formation of entrepreneurial character in the pesantren is not merely oriented toward economic competence but represents a holistic process integrating the values of honesty (siddiq), trustworthiness (amanah), discipline, and social responsibility. These values are cultivated through integrated learning practices, such as sorogan and bandongan methods, direct involvement in pesantren business units, and continuous moral guidance from the caregivers. This study contributes to the development of a tarbiyah-based Islamic entrepreneurship education model that positions pesantren as an alternative educational paradigm for producing ethical, character-driven entrepreneurs who are oriented toward the welfare of the Muslim community.